PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN MASYARAKAT KECAMATAN BATU AJI - Dompak, Timbul; Salsabila, Lubna; Khodijah, Paramita; Barimbing, Suryani (JURSIMA, 2023)
This research is aimed at analyzing the influence of service quality (X) on community satisfaction in Batu Aji District (Y). The approach in this research uses quantitative methods, by distributing questionnaires to respondents. The research sample was 100 people. The results of research using the comparison method between t-count and t-table, the t-table value obtained with a total of 100 data is 1,984, while the t-count value for service quality is 12,575, because t-count (12,575) > t-table (1,984). Based on the data above, the significance value (Sig.) of 0.000 is smaller than <0.05 probability, so H0 is accepted, Ha is rejected, therefore it means that there is an influence of service quality (X) on satisfaction (Y). Meanwhile, the determination results obtained obtained an R value of 0.786, meaning 78.3%, while an R2 value of 0.617, meaning 61.7%. The Community Satisfaction variable can be explained by service quality as an independent variable and the remainder (100%-61.7%=38.3%) is not in the research.